TRENDS AND CONCEPTS OF MARKETING COMMUNICATIONS AT THE MODERN STAGE OF COMMODITY MARKET - Vladimir A. Polyakov; Andrey A. Romanov (Статистика и экономика, 2016)
The article considers and justifies the modern concepts and trends of marketing communications. It deals with examples of emerging communication technologies, proposes the system of the evolution concepts of marketing communications and characteristics of the life cycle of the advertising market. Development directions of the concepts of marketing communications are given in the article.